'Multiplying owners, not artworks': some retrospective reflections on the intention and reception of Eduardo Chillida's sculptures in public space. (November 2018) - Schmidt, Sabine Maria
Abstract : Cities and their spaces are changing. That is the way of things. But what will the future hold for the legacy of public art? Over the past fifteen years, debates on art in public space have once again radically changed against the backdrop of neoliberal and post-democratic structures and criteria. The article focuses on the ten-year anniversary of Chillida's death in 2012 and some observations related to the financial crisis in 2008. While the canonization of the artist in the art market is unlikely be shaken in the future, the evaluation of public spaces and the appreciation of public sculpture is again subject to serious challenges. Not only art, but also the institutions that represent and canonize it are being put to the test. Against this background, the article shows how differently the aspects of 'site-specificity' and memorialization in Chillida were developed at an early stage on the path to his 'monumental sculpture in the spirit of modernity'.